PENGARUH INTELLECTUAL CAPITAL, ISLAMIC CORPORATE SOCIAL RESPONSIBILITY DAN ZAKAT TERHADAP KINERJA KEUANGAN BANK UMUM SYARIAH PERIODE 2012-2020 - Medy Putri Maulidia; Rizal Fahlevi (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
Knowledge is an important requirement for a company, especially in service companies such as sharia banking, where operational activities directly interact with customers, so that existing human resources must have adequate skills and knowledge. Based on a brief description of the background, the formulation of the research problem (1) does Intellectual Capital affect the financial performance of Islamic commercial banks for the 2012-2020 period? (2) does Islamic Corporate Social Responsibility affect the financial performance of Islamic commercial banks for the period 2012-2020? (3) Does Zakat affect the financial performance of Islamic commercial banks for the period 2012-2020? (4) whether Intellectual Capital, Islamic Corporate Social Responsibility and Zakat affect the financial performance of Islamic commercial banks for the period 2012-2020. This study aims to determine the effect of Intellectual Capital, Islamic Corporate Social Responsibility, and Zakat on the financial performance of Islamic commercial banks for the period 2012-2020. This research is a quantitative research. The population of this research is all Islamic Commercial Banks in Indonesia. This research uses purposive sampling method. The sample used in this study were 4 Islamic Commercial Banks that met the required criteria. The data used is secondary data and the analysis method used is panel data regression analysis. The results of the research show that partially the results